Genome-wide variation in the pinewood nematode Bursaphelenchus xylophilus and its relationship with pathogenic traits. (December 2015) - Palomares-Rius, Juan; Tsai, Isheng; Karim, Nurul; Akiba, Mitsuteru; Kato, Tetsuro; Maruyama, Haruhiko; Takeuchi, Yuko; Kikuchi, Taisei
Abstract Background Bursaphelenchus xylophilus is an emerging pathogenic nematode that is responsible for a devastating epidemic of pine wilt disease across Asia and Europe. In this study, we report the first genome-wide variation analysis of the nematode with an aim to obtain a full picture of its diversity. Methods We sequenced six key B. xylophilus strains using Illumina HiSeq sequencer. All the strains were isolated in Japan and have been widely used in previous studies. Detection of genomic variations were done by mapping the reads to the reference genome. Results Over 3 Mb of genetic variations, accounting for 4.1 % of the total genome, were detected as single nucleotide polymorphisms or small indels, suggesting multiple introductions of this invaded species from its native area into the country. The high level of genetic diversity of the pine wood nematode was related to its pathogenicity and ecological trait differences. Moreover, we identified a gene set affected by genomic variation, and functional annotation of those genes indicated that some of them had potential roles in pathogenesis. Conclusions This study provides an important resource for understanding the population structure, pathogenicity and evolutionary ecology of the nematode, and further analysis based on this study with geographically diverseB. xylophilus populations will greatly accelerate our understanding of the complex evolutionary/epidemic history of this emerging pathogen.